Iridoid constituents from the ant plant Hydnophytum formicarum - Hanh, Nguyen Phuong; Toan Phan, Nguyen Huu; Dieu Thuan, Nguyen Thi; Vien, Le Thi; Hong Hanh, Tran Thi; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Using various chromatographic methods, four iridoids namely asperulosidic acid (1), deacetylasperulosidic acid (2), 6α-hydroxygeniposide (3), and 10-hydroxyloganin (4), were isolated from the methanol extract of the ant plant Hydnophytum formicarum. The structural elucidation was done using 1D and 2D-NMR experiments and comparison of the NMR data with reported values. This is the first report of these compounds from H. formicarum.